Impact of Parenting Styles, Parental Involvement, and Family Environment on Child Behavior - Ramzan, Ghazala; Kamran, Muhammad (Kashmir Journal of Academic Research and Development, 2026)
The behavior of children is influenced by various environmental and societal factors with parenting behaviors, parental engagement and family setup being the major ones. The realization of the impact of these factors on the emotional, social and behavioral growth of children has been of more significance in the modern developmental and educational studies. In this paper, we look at how parenting styles, parental involvement and family environment influence the behavior of children based on current empirical research and theoretical models. Authoritative, authoritarian, permissive and neglectful parenting styles have a great impact on the emotional regulation of children, social competence and the overall outcome in terms of behavior. In the same way, the parental participation in academic and social lives of children offers positive behavioral adaptation, motivation, and psychological well-being. Besides that, the extended family background such as communication pattern, emotional climate, socioeconomic status, and family relations is very instrumental in determining behavioral development in children. Positive behaviors are encouraged by a positive and supportive family environment, and dysfunctional family dynamics can result in aggression, anxiety and behavioral problems. The results indicate that authoritarian parenting, regular interactions with parents, and an optimum family climate play a crucial role in promoting positive behavioral results in children. It is argued in this study that facilitating the psychological well-being and social growth among children could be achieved by promoting good parenting habits and enhancing family relationships.
Keywords: parenting style; parental participation; family setting; child behavior; child development